Estimating Transpiration of Whole Grapevines under Field Conditions - Myburgh, P.A (South African Journal of Enology and Viticulture, 2016)
yield, growth and quality. Diurnal whole-plant transpiration, to be used in combination with a soil evaporation model to estimate vineyard evapotranspiration, was quantified by measuring sap flow in grapevines. Sap flow was measured in grapevine trunks by means of the heat pulse velocity technique. Diurnal sap flow ranged from almost zero to c. 5 L/d per grapevine under various atmospheric, viticultural and soil conditions. Sap flow showed good linear correlation with leaf area per grapevine and reference evapotranspiration (ETo). Grapevines with similar leaf area trained onto horizontally orientated trellis systems transpired more than those on vertical trellises under the same atmospheric conditions. Approximately 90% of the variation in daily transpiration could be explained by means of multiple linear regression, with leaf area and daily ETo as the independent variables. However, grapevines with horizontal and vertical canopies required slightly different models.